Coal ash induced ring formation in a pilot scale rotary kiln for low-grade iron ore direct reduction process: Characterization and mechanism. (15th February 2022) - Yi, Lingyun; Zhang, Nan; Liang, Zhikai; Wang, Lin; Xiao, Huarong; Huang, Zhucheng
Graphical abstract: Highlights: Direct reduction of low-grade iron ore was performed by a coal fired rotary kiln. Actual running status and furnace burden of rotary kiln were in-situ investigated. Ring formation mechanism was revealed by given the real physicochemical condition. Hedenbergite and fayalite developed by coal ash and ore induced key molten phase. Corresponding solutions were suggested for practical rotary kiln operation. Abstract: For economic utilization of low grade iron ore resource, a pilot scale study of iron ore direct reduction by rotary kiln (ϕ1.5 m × 15 m) was carried out. In this work, the actual furnace burden and temperature distribution status in rotary kiln were in-situ measured. The location and typical physicochemical condition in rotary kiln for ring substances generation were verified. SEM equipped with EDX, XRD and optical microscopy were applied to analyze the characteristics of ring substances. Extra lab experiments and phase diagram calculation with the help of Factsage 7.0 were performed to reveal the ring formation mechanism. Results showed that ring substances emerged at 5 ∼ 6 m zone of rotary kiln, with high temperature, coal proportion, and metallic iron content of pellets in this region. Pellets bonded together by the sintering of metallic iron on surface, then, molten wrappage cemented them to refractory of rotary kiln forming the ring. Hedenbergite and fayalite produced by interaction of coal ash and iron ore powder developed the molten wrappage. The new understanding of ring formation promised potential for its application in coal fired rotary kiln operation.